TWO TYPES OF ONGONITE AND ELVAN - Dergachev V.B. (My University, 1989)
Comparison of rocks studied shows that the largest differences between ongonites and elvans from different granite associations are those in the oxides of iron, calcium and phosphorus. The ongonite associated with plumasitic rare-metal granite resembles in composition the average, standard ongonite. One would expect the main differences between ongonites and elvans to be in terms of their barium and strontium concentrations, but this is not observed. Their main difference is in the tin concentrations, which are very high. The average compositions of 17 different dikes show coefficients of tin concentration ranges from 18 to 108, as is also typical of plumasitic rare-metal granite. On the other hand, ongonites and elvans associated with subalkalic granites exhibit fairly high or very high concentrations of tungsten and molybdenum. Whatever differences there exist in the contents of rare alkali metal elements and fluorine seem to be caused by regional differences in the composition of the dike belt. Thus, depending on which particular geochemical type of rare-metal granite they are associated with, dike rocks can be subdivided into ongonites or elvans.